The magic shoes of IPSAS: Will they fit Turkey? - Selver Seda ADA; Johan CHRISTIAENS (Transylvanian Review of Administrative Sciences, 2018)
In this study, we seek to further delineate the reasons for the existence of shortfalls in the level of formal and material harmonization regarding the accrual-based rules in International Public Sector Accounting Standards (IPSAS) by analyzing the law, the executive order and the Turkish Central Government Public Reports from2010to 2014 (using a mixed method approach).We highlight that coercive pressure itself is insufﬁcient for improving substantive performance and changing the internal structures of organizations, instead, such pressures cause decoupling in ﬁnancial reporting. As a new ﬁnding in the context of a developing country, we suggest that there are several discrepancies between the law and the executive order. Moreover, we conclude that there are emerging country-speciﬁc reasons affecting the gap in the harmonization levels, including a lack of social pressure which tends to be prominent in developed countries, state domination over both civic matters and the private sector, and translation problems that arise during the adoption process.